2004
DOI: 10.1111/j.0022-1112.2004.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the pattern of antipredator behaviour between hatchery‐reared and wild European sea bass juveniles

Abstract: Shoals of hatchery-reared and wild sea bass juveniles Dicentrarchus labrax were tested for differences in their antipredator responses towards a potential live predator, the eel Anguilla anguilla. Eight experimental shoals (i.e. replicates), each composed of 15 individuals from the same stock of juveniles (i.e. wild or hatchery), were video recorded for 5 min before and after predator exposure. A set of behavioural variables were measured during the pre-stimulus and stimulus phases of each test and compared be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 29 publications
4
45
0
Order By: Relevance
“…This may reflect the higher levels of stress in our study, in which the fish were much larger than those used in the previous study and may, therefore, have been more difficult to handle. The fish remained motionless in the start box for a large proportion of the time, which resembles the characteristic "freezing behaviour" described for fish subjected to stressful events (Malavasi et al 2004;Millot et al 2009). Once out of this zone, both categories of fish spent most of their time in the zone located near the congener and in the area on the opposite side.…”
Section: Swimming Activity and Spatial Distributionsupporting
confidence: 58%
“…This may reflect the higher levels of stress in our study, in which the fish were much larger than those used in the previous study and may, therefore, have been more difficult to handle. The fish remained motionless in the start box for a large proportion of the time, which resembles the characteristic "freezing behaviour" described for fish subjected to stressful events (Malavasi et al 2004;Millot et al 2009). Once out of this zone, both categories of fish spent most of their time in the zone located near the congener and in the area on the opposite side.…”
Section: Swimming Activity and Spatial Distributionsupporting
confidence: 58%
“…Other possible factors that could have contributed to the sea bass' inshore migration could be either a greater availability of more suitable prey items in shallow waters, and/or the occurrence of predators (Conger conger) at the reef site. In fact, experiments carried out on hatchery-reared individuals obtained from the same broodstock used in this study showed that the young sea bass had fully developed antipredator responses, even though they displayed a lower reactivity to predators in respect to wild juveniles [48]. According to other studies [44,45,46], a positive relationship was found between the size of recaptured sea bass and depth, showing that, as fish grew, they gradually migrated towards greater depths aggregating around man-made structures, such as artificial reefs and mussel cultures.…”
Section: Resultsmentioning
confidence: 68%
“…The decision to instantly move towards illuminated areas of the tank was probably driven by the intense schooling behaviour, which is well-known species characteristic [27] that ensures lowered predation, energetic advantages and favorable conditions. Sea bass individuals from this group were not motivated to reverse crossings in the dark compartment, even though they have to starve.…”
Section: Discussionmentioning
confidence: 99%